42-(2c+)=4(c+6)+c

Simple and best practice solution for 42-(2c+)=4(c+6)+c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42-(2c+)=4(c+6)+c equation:



42-(2c+)=4(c+6)+c
We move all terms to the left:
42-(2c+)-(4(c+6)+c)=0
We add all the numbers together, and all the variables
-(+2c)-(4(c+6)+c)+42=0
We get rid of parentheses
-2c-(4(c+6)+c)+42=0
We calculate terms in parentheses: -(4(c+6)+c), so:
4(c+6)+c
We add all the numbers together, and all the variables
c+4(c+6)
We multiply parentheses
c+4c+24
We add all the numbers together, and all the variables
5c+24
Back to the equation:
-(5c+24)
We get rid of parentheses
-2c-5c-24+42=0
We add all the numbers together, and all the variables
-7c+18=0
We move all terms containing c to the left, all other terms to the right
-7c=-18
c=-18/-7
c=2+4/7

See similar equations:

| 8x+-18x=-10 | | -y=-y+1 | | 1(-x)-(-4)=(-x)-x+1 | | −5x2+100x−520=0 | | -8d−1=-8d−4 | | 22=4s-6s | | 8−8r=-8r+5 | | -5f=-5−5f | | 7-5=1/3(x+12) | | 9m=9m−4 | | -4(1-9h)=-31 | | -3z−8=-2z | | 8f=7f+f | | (x)=4x^2+x+5 | | 3c+6-7=-16 | | 10q=1+9q | | -9c+4=-10c | | -9s+5s=-4s | | 9x+45=8x+59 | | 3v=1+3v | | 2r+5=19r= | | 3x+4=4+8x | | 15-3n=4(6n+8) | | 121-u=173 | | 8−-3w=20 | | 7x17=73 | | 3(x-2)-x=3 | | 2(w+3)=16 | | -26=7(4z+9) | | B=x+93∘ | | 6(2x-9)=-90 | | -4(2x+6)=-112 |

Equations solver categories